2018
DOI: 10.1002/ejoc.201800703
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 7‐Bromo‐1,3‐diazapyrenes

Abstract: An efficient synthetic route towards previously inaccessible 7‐bromo‐1,3‐diazapyrenes through an in‐melt peri‐cyclization of readily available 7‐(5‐bromo‐3,4‐dihydropyrimidin‐4‐yl)‐1H‐perimidines is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Perimidines are a very important class of chemical compounds, owing to their biological activity and their application as ligands . In addition, 1 H ‐perimidines are common starting materials for the synthesis of azapyrenes, which are promising materials for the manufacturing of organic semiconductor devices …”
Section: Figurementioning
confidence: 99%
“…Perimidines are a very important class of chemical compounds, owing to their biological activity and their application as ligands . In addition, 1 H ‐perimidines are common starting materials for the synthesis of azapyrenes, which are promising materials for the manufacturing of organic semiconductor devices …”
Section: Figurementioning
confidence: 99%
“…This compound has been prepared by thermal cyclization, by using a lengthy nine step-sequence, by PPA (polyphosphoric acid)-induced Beckmann rearrangement, and by peri -annulation with sym -triazines . In the course of the development of Pd-catalyzed cross-coupling reactions, , a number of di- and triazapyrenes and related molecules have been published. , Recently, the group of Kozaki published an intramolecular Cu­(I)-catalyzed C–H functionalization approach, while Han et al applied the classical Bischler–Napieralski cyclization of amide precursors …”
Section: Introductionmentioning
confidence: 99%
“…24 It was also shown that unlike most other pyrimidines, 5-bromopyrimidine 10 did not react according to this general scheme, forming monoalkylation products 11 instead (Scheme 2). 24,25 Apparently, this process is related to a Friedel-Cras type S E Ar alkylation reaction, in which pyrimidine in protonated form serves as an Scheme 1 Synthetic approaches towards 4-arylpyrimidines.…”
Section: Resultsmentioning
confidence: 99%